Design Of A Clothing Sewing Service System At Bucik Rendo Tailor User Prototype Method - Bima Herbudi; Marissa Utami; Guntur Alam; Surya Ade Saputera (Jurnal Media Computer Science, 2026)
This study aims to design a clothing sewing service information system at Bucik Rendo Tailor using the prototype method. The problem that occurs in this sewing service business is the data management process that is still done manually, such as recording customer data, orders, payment transactions, and business reports. This condition causes frequent recording errors, difficulties in data retrieval, and slow service to customers. To overcome these problems, this study uses the prototype method because it can help developers understand user needs more clearly through a gradual evaluation and improvement process. Data collection was carried out through observation, interviews, literature studies, and documentation studies. The results of the study are in the form of a system design that includes a Data Flow Diagram (DFD), Entity Relationship Diagram (ERD), database design, and user interface design. The designed system has features for managing customer data, products, orders, transactions, work status, and reports. With this system design, it is expected to help improve the effectiveness of clothing sewing service business management, facilitate service to customers, and serve as a reference in the development of a web-based sewing service information system in the next implementation stage.